Potensi e-Modul dalam Pembelajaran Bahasa Arab pada Era Globalisasi - Mohd. Yazid, Mohd. Taqwudin; Wan Sulong, Wan Muhammad; Mustapha, Nik Farhan; Abdul Jabar, Mohd Azidan (Universiti Teknologi Malaysia, 2023)
Computer-Assisted Language Learning and e-learning are among the features that characterize Arabic language learning in the 21st century and the era of the Fourth Industrial Revolution. The presence of e-modules that incorporate these features into the online Arabic language learning landscape has successfully ensured the continuity of teaching and learning processes amidst the COVID-19 pandemic. This study aims to explore the potential and effectiveness of e-modules in Arabic language teaching and learning. The study adopts a qualitative approach and utilizes a literature review methodology. Data collection involves reviewing past studies and relevant documents, which are then analyzed descriptively. The findings reveal five main potentials identified, namely, e-modules operating through various Internet of Things (IoT) based products, e-modules serving as a virtual learning alternative, e-modules that can be used anytime and anywhere, e-modules rich in multimedia elements, e-modules employing personalized learning approaches, and e-modules fostering responsible technology use. The study also suggests further in-depth research in the future regarding the trends in the development of Arabic language e-modules based on the insights gained from previous studies, in order to strengthen this field.